On the Significance of Divje babe I Cave for the Stratigraphy, Sedimentology, and Chronology of Palaeolithic Cave Sites in Slovenia - Matija Turk; Janez Turk (Arheološki Vestnik, 2023)
The article reviews the development and interpretation of procedures used in the study of the sedimentary sequence of the Divje babe I Palaeolithic cave site. The data were obtained from publications, archives, and personal information provided by Ivan Turk, who directed the excavations and directed the laboratory investigations. The profile of Divje babe I is currently the best researched and chronologically defined Late Pleistocene cave profile in Slovenia. For the first time, various sedimentological and other data from the standard profile were upgraded with the same data obtained on standardized ground plan surfaces and depths. A large spatial (lateral) variability was discovered, associated with generally contemporaneous but different cave microenvironments, which were crucially influenced by different amounts of water in all aggregate states. Without taking into account temporal and spatial dimensions, it would not be possible to combine all statistical sets of collected data on sediments, their contents, and climatic parameters into a unified system.